The differences in behaviour and feeding success of tame Mallard ducklings Anas platyrhynchos in the presence of high and low fish populations at a gravel pit site, with reference to wild brood distribution - Phillips, V E; Wright, R M (Wildfowl, 1993)
Survival of Mallard ducklings less than two weeks old is poorer at flooded gravel pits than at natural lakes. This has been attributed to inadequate invertebrate prey, particularly a lack of chironomid midges, in gravel pits. At Great Linford gravel pit complex the diet of several common species of coarse fish has been shown to overlap with that of ducklings. The removal of the adult fish population of the wildfowl reserve lakes in 1987 led to a considerable increase in submerged weed beds and in benthic invertebrates, including chironomid larvae. The number of broods reared at these lakes increased. Surveys of all the lakes on the site found more wild Mallard broods at lakes known to have low fish densities than at those that have been regularly stocked for angling. In this study groups of tame Mallard ducklings were taken to areas of high and low fish densities and were consistently found to lose less weight when feeding in fish-free conditions than at sites with a high fish density. (In the experimental conditions duckling rarely gained weight.) In low fish conditions they also spent more time actively feeding but travelled less distance during each trial. It is suggested, therefore, that they would use less energy and be less conspicuous to predators (e.g pike, mink, fox) than ducklings at sites with high fish density. Sampling at the trial sites confirmed that significantly more invertebrate food was available where there were no adult fish. These results add to the evidence that low fish densities are beneficial to duckling survival.